Kontribusi Pemikiran Linguistik al-Anbari Terhadap Penafsiran Kosa Kata Kontranimi - Mahyudin Ritonga (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2018)
This paper wants to describes the contribution of al-Anbari's thought in the interpretation of the verses of the Koran, this is inseparable from al-Anbari's expertise not in the field of interpretation but linguists. The main source of this research is the work of al-Anbari entitled "al-Adhdad" while the secondary source is the work of al-Anbari in other fields and the work of others that are related to the research theme. The results showed that al-Anbari as a nahwu Kufah expert had different thoughts from other Kufah scholars both in the fields of syntax and morfology. His thinking in the problem of syntax and morfology seems to have a significant contribution in providing an understanding of the verses of the Koran, especially the verses in which the word at-tadhad is used. The contribution of his thoughts can be understood from his interpretation of the use of letters, idioms, verbs, name of subject, name of object, circumstance, and derivations in the Koran.